2020
DOI: 10.1590/2317-1782/20202018285
|View full text |Cite
|
Sign up to set email alerts
|

Quando exercícios de fortalecimento da língua refletem na região cervical

Abstract: RESUMO Objetivo: Comparar o impacto do exercício isocinético “sucção da língua contra o palato” na região cervical em participantes Classe I e Classe II/2.ª Divisão, considerando a média e a simetria do Root Means Square (RMS) dos músculos supra-hióideos e suboccipitais, e relatos sensoriais cervicais. Método: Onze participantes Classe I e 19 Classe II/2.ª Divisão, ambos os gêneros, média de idade 33,4 ±14,1 anos. Para análise da média do RMS e da simetria, realizou-se eletromiografia dos músculos suboccipit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The electrographic studies of Nascimento et al 23 found asymmetry in the suprahyoid muscular and occipital activities in Classes I and II/2nd Division during an isometric suction exercise. In this experiment, Class I recovered its symmetry, while Class II/2nd Division remained asymmetrical and with the presence of discomfort in the cervical region by overload.…”
Section: Vertical Alignment Of the Mandible Skull And Cervical Spinementioning
confidence: 94%
“…The electrographic studies of Nascimento et al 23 found asymmetry in the suprahyoid muscular and occipital activities in Classes I and II/2nd Division during an isometric suction exercise. In this experiment, Class I recovered its symmetry, while Class II/2nd Division remained asymmetrical and with the presence of discomfort in the cervical region by overload.…”
Section: Vertical Alignment Of the Mandible Skull And Cervical Spinementioning
confidence: 94%
“…The craniomandibular system is widely studied in the scientific community and the interinfluence of its structures, one on the other, still generates discussions 2 . In comparative studies of Angle's Classes I and II/ 2nd Division, such as Nascimento et al 3 , it was observed that the participants of this last class, unlike the first, suffer significant impacts in the cervical region when the tongue muscles are overloaded by isometric suction exercises 3 .…”
Section: Introductionmentioning
confidence: 99%